The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1096/fj.201600827r
|View full text |Cite
|
Sign up to set email alerts
|

Use of LDL receptor—targeting peptide vectors for in vitro and in vivo cargo transport across the blood‐brain barrier

Abstract: The blood-brain barrier (BBB) prevents the entry of many drugs into the brain and, thus, is a major obstacle in the treatment of CNS diseases. There is some evidence that the LDL receptor (LDLR) is expressed at the BBB and may participate in the transport of endogenous ligands from blood to brain, a process referred to as receptor-mediated transcytosis. We previously described a family of peptide vectors that were developed to target the LDLR. In the present study, BBB models that were derived from wild-type a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 55 publications
(102 reference statements)
2
58
0
Order By: Relevance
“…About approx. 25% or more of the total cholesterol in human body is located in the brain to maintain neuronal physiology 30) ; however, in cholesterol homeostasis in the brain, the uptake from blood circulation based on RMT has little importance in usual condition due to de novo synthesis in the brain. Notwithstanding, transendothelial drug transfer based on RMT via LDLR is useful.…”
Section: Receptor-targeting Peptides As Ligandsmentioning
confidence: 99%
“…About approx. 25% or more of the total cholesterol in human body is located in the brain to maintain neuronal physiology 30) ; however, in cholesterol homeostasis in the brain, the uptake from blood circulation based on RMT has little importance in usual condition due to de novo synthesis in the brain. Notwithstanding, transendothelial drug transfer based on RMT via LDLR is useful.…”
Section: Receptor-targeting Peptides As Ligandsmentioning
confidence: 99%
“…Depending on the different types of apolipoproteins present on their surface, the lipoproteins are captured by lipoprotein receptors of specific cells. Drug nanoparticles conjugated with apolipoprotein domains have been developed with limited brain penetration due to their large size and their competition with circulating endogenous ligands [108,109].…”
Section: Combinations Of Drugs Targeting Receptor-mediated Transportmentioning
confidence: 99%
“…Additionally, the physiological activity of the receptor must be retained, and importantly, not changed as a consequence of its use as drug delivery mediator across the BBB. Among the highly expressed BBB receptors exploited for drug delivery to the brain are receptors for transferrin, 61 low-density lipoprotein, 62 and insulin. 63 A number of studies have demonstrated that the TfR and the low-density lipoprotein receptors (LDLRs) are suitable to target for drug delivery across the BBB due to the fact that these receptors may facilitate drug transcytosis.…”
Section: Receptor-mediated Transcytosismentioning
confidence: 99%